Factors influencing HACCP implementation in the food industry - MILIOS (Κ. ΜΗΛΙΟΣ), K.; DROSINOS (Ε. ΔΡΟΣΙΝΟΣ), E. H.; ZOIOPOULOS (Π.Ε. ΖΩΪΟΠΟΥΛΟΣ), P. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
HACCP application in food processing plants could improve food safety and lead to a reduction of food-borne diseases. Apparent lack of HACCP implementation in several food businesses may be due to presence of various technical barriers. The aim of this review is to explore the lists of motives and barriers to implementation of the HACCP system as outlined in the published literature and to evaluate respective impact. Lack of awareness of HACCP, no perceived benefits, lack of training, management regressions, variability of production lines and individuality of each product, variability of the consumers’ demands and small size of an enterprise have been found to have negative effects on implementation and performance of a HACCP system. Also, costs of development, as well as application and maintenance of the system seem to constitute a severe constraint. According to the authors’ opinion, lack of management commitment, in addition to lack of personnel training and costs are the main constraints to appropriate implementation of HACCP. On the other hand, motivation for HACCP application provides an improvement of processing procedures’ efficiency, decrease of recalls, regulatory demands, enhancement of firm reputation, costs reduction, customers’ demands, previous experiences with food safety issues, trained staff and management decision. Finally, legislation cannot provide adequate motivation for appropriate HACCP implementation, so that market motivation is, in our view, the key factor that can lead to management commitment.